2005
DOI: 10.1242/jcs.02436
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein kinase C α-dependent signal to ERK1/2 activated by αVβ3 integrin in osteoclasts and in Chinese hamster ovary (CHO) cells

Abstract: We identified a novel protein kinase C (PKC)α-dependent signal to extracellular signal-regulated kinase (ERK)1/2 in mouse osteoclasts and Chinese hamster ovary (CHO) cells, specifically activated by the αVβ3 integrin. It involves translocation (i.e. activation) of PKCα from the cytosol to the membrane and/or the Triton X-100-insoluble subcellular fractions, with recruitment into a complex with αVβ3 integrin, growth factor receptor-bound protein (Grb2), focal adhesion kinase (FAK) in CHO cells and proline-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 63 publications
3
47
0
Order By: Relevance
“…Whether PKC␣ may up-regulate directly osteoblast gene expression is an interesting question. PKC␣ was found to be involved in ERK1/2 activation in osteoclasts (64). However, we found that molecular inhibition of PKC␣ but not ERK1/2 reduced osteoblast gene expression in MT FGFR2 cells, suggesting that ERK1/2 does not act downstream of PKC␣ in these cells.…”
Section: Discussionmentioning
confidence: 53%
“…Whether PKC␣ may up-regulate directly osteoblast gene expression is an interesting question. PKC␣ was found to be involved in ERK1/2 activation in osteoclasts (64). However, we found that molecular inhibition of PKC␣ but not ERK1/2 reduced osteoblast gene expression in MT FGFR2 cells, suggesting that ERK1/2 does not act downstream of PKC␣ in these cells.…”
Section: Discussionmentioning
confidence: 53%
“…Our observations, however, may be cell-type specific, because other groups using similar membrane dyes have concluded that PLC␦ 1 PH domain and mGAP43 accumulation in localized regions of the plasma membrane is not caused by locally increased membrane area but instead is attributed to rafts (Huang et al, 2004;Golub and Caroni, 2005). Recently, PKC␣ has been demonstrated to associate with detergent-insoluble fractions in a Ca 2ϩ -dependent manner attributed to raft binding (Rucci et al, 2005). However, the correlation between lipid rafts in cells and detergent-insoluble fractions derived from cells continues to be challenged (van Rheenen et al, 2005).…”
Section: Targeting Of Pkc␣ and The Isolated Pkc␣ C2 Domain To Puncta mentioning
confidence: 71%
“…For example, the extracellular matrix initiates signaling by binding to integrins. PKCα in osteoclasts associates with αvβ3 integrin and activates ERK1/2, thereby regulating cell migration and bone resorption (Rucci et al, 2005). Interestingly, αvβ3 integrin has been reported to be localized on the basolateral membrane in osteoclasts (Duong et al, 2000).…”
Section: Potential Relevance Of Pkc Targeting To the Basolateral Membmentioning
confidence: 99%
“…The activity of conventional protein kinase isozymes (cPKCs; α, βI, βII and γ) is stimulated by diacylglycerol, Ca 2+ and phosphatidylserine; that of novel isozymes (nPKCs; δ, ε, η and θ) by diacylglycerol and phosphatidylserine; whereas atypical PKC isoforms (aPKCs; ζ and ι) are activated by phosphatidylserine, but are independent of Ca 2+ and phorbol esters. Several PKC isozymes have been identified in osteoclasts, including α, δ and ε (Teti et al, 1995), with more recent evidence also revealing the expression of β and ζ in these cells (Williams et al, 2000;Rucci et al, 2005).…”
Section: Introductionmentioning
confidence: 99%